Targeting cancer cells: from historic methods to modern chimeric antigen receptor (CAR) T-Cell strategies - Saleh, Kochar Khasro; Dalkilic, Semih; Dalkilic, Lutfiye Kadioglu; Hamarashid, Bahra Radhaa; Kirbag, Sevda (Amer Inst Mathematical Sciences-Aims, 2020)
Cancer therapy and diagnosis have long been challenges for humans. Despite accumulated knowledge and information, there are many complications and difficulties with cancer therapy and diagnosis. The challenges of cancer treatment are modified according to the new forms that have been discovered by researchers. Each stage of development has involved new techniques for cancer therapy, culminating in the modern immunotherapy approach using chimeric antigen receptor (CAR) cytotoxic T lymphocytes. This strategy is an example of the latest version of cancer cell therapy. Chimeric antigen receptor T-cell therapy drew interest soon after its implementation by researchers as a new strategy to control various types of cancer cells, and it is considered a living drug in the body that detects and destroys cancer cells in a long-term manner, with CAR T-cells remaining as memory cells. CAR T-cell therapy has shown remarkable effects against both primary acute lymphoblastic leukemia (ALL) and relapsed ALL, with a high remission rate observed in adults and children (approximately 90%). Although the use of CAR T-cell therapy for solid tumors has encountered obstacles associated with the microenvironment and immunosuppression, researchers are poised to improve effective CAR T-cell therapy for solid tumors. In this mini review, we describe some attempts that have applied CAR T-cells from the past and present; in addition, it contains many aspects of new anticancer strategies featuring CAR T-cells, especially CAR T-cell killing mechanisms.
Keywords: cancer; immunotherapy; chimeric antigen receptor T-cell